Educational Design for Adolescents Aware of Reproductive Health in an Effort to Prevent Stunting in Singkawang Public Health Center - Dwi Sulistyawati; Ernawati; Nikki Susanti (HealthCare Nursing Journal, 2023)
Stunting is one of the targets of the Sustainable Development Goals (SDGs) which is included in the 2nd sustainable development goal. One of the causes of stunting is the mother's age which is too young. Interventions to prevent an increase in educational design for adolescents aware of reproductive health. as an effort to prevent stunting in health education activities. This research activity used a Quasi Experiment pre & post test with the control group. The sample in this research are 40 respondents. This research was conducted in the working area of North Singkawang Health Center I. Evaluation of the implementation of this research activity using the knowledge and attitudes of the ordinal scale. Data analysis using Wilcoxon study. The research is targeted to have met the Technology Readiness Level scale, which is when the intervention is started, the basic principles are observed, practical applications can be explored/developed. The application is still speculative and there is no detailed evidence or analysis to support the assumptions used and the examples are still limited to paper studies. The results showed an increase in knowledge about stunting prevention with a p value of 0.00 and an increase in attitude with a p value of 0.00 so that RS2R can be used as an activity that can be implemented in the wider community, especially adolescents.